Community institutions in water governance for sustainable livelihoods - Pradhan, P.; Khadka, Manohara; GC, Raj K.; van Koppen, Barbara; Rajouria, A.; Pandey, V. P. (Practical Action Publishing, 2022)
Successful community institutions in the global South, which are contributing to livelihoods’ improvement while conserving water and other natural resources, can sustainably build the resilience that policy makers at different tiers are seeking. This article assesses different models of community institutions in Nepal in governing water resources from various lenses, based on Ostrom’s and others’ design principles, including bricolage. Illustrated by three empirical cases, it analyses key features of community institutions in integrated water governance, their contributions to health, nutrition, food security, and environmental conservation, and ways for empowering these institutions as viable and sustainable solutions to address various livelihood challenges. However, inequalities along gender, caste, and ethnicity lines persist. We argue that the recently established local governments under the federal system in Nepal provide new opportunities for gender and social inclusion.